PERBEDAAN LAMA WAKTU PAlANAN TERHADAP KANDUNGAN TIMBAL PADA MAKANAN JAlANANGORENGAN YANG DIJUAL DI ALUN-ALUN KOTA MADIUN TAHUN 2014 - Evi Damayanti; Rusmiati .; Lilis Prihastini (GEMA LINGKUNGAN KESEHATAN, 2014)
One of the pollutants produced by motor vehicles is lead (Pb). Lead (Pb) is a toxic anddangerous heavy metal to the environment and have a systemic impact in human bodies. Lead (Pb) canenter the body through inhalation, snacks sold on the roadside without cover. This will be even moredangerous if the food is exposed for a long time. The purpose of this research was to determine the levelsof lead (Pb) in snacks based on exposure time during peddling in Madiun square in 2014.The research followed pre-experimental design using posttest only protocol. Data collection wasdone by sampling, documentation and observation. The population under study was the food peddlers offried soybean cakes along the roadside around Madiun square. The samples to be examined were friedsoybean cakes, in 3 replications and to be performed 3 times in each treatment and the exposure time ofthe 9 samples. Sampling was drawn by random sampling and data was to subjected to descriptiveanalysis.The results obtained from this research include the facts that all samples did contain heavymetals lead (Pb). The average levels of lead (Pb) before exposure was 0.01 .rnq / I, after an hourexposure was 0,021 mg / I, and after 2 hours of exposure was 0,033 mg / I. The concentration of lead(Pb) remained below the designated requirement, the Threshold Limit Value established by the DirectorGeneral of POMNo. HK.00.06.1.52.4011 regarding the maximum limit of lead metal contamination in food.One way ANOVA statistical test results obtained (p) a so that HO means no Significant differencebetween exposure times i.e. a hours, 1 hour, and 2 hours in term of the lead content.The conclusion of this study is: there was no significant difference in lead content in snacks,namely the soybean cakes with the exposure time of 0 hours, 1 hour, and 2 hours, although there was anincrease based on the length of exposure time. Pedlers are encouraged to use a cloth cover / Stelling toreduce contamination of lead (Pb). Further research is necessaryto study the aerial concentration of leadin Madiun square.